The Qur’anic approach in rehabilitation of the behavioural disorders and criminal tendencies: Applied study on rehabilitation centre for repentant in Kuwait / Abdullah A S A AlMutairi - Abdullah A S A , Almutairi (2023)
A lot of societies suffer from the problem of behavioral disorder and criminal propensity among many individuals. This led to an increase in crime and the need for rehabilitation and treatment. Rehabilitation centers for people with behavioral disorders and criminal tendencies were established in many countries to integrate this group into society and make them useful people for themselves and society. The study discussed the Holy Qur’an’s approach in evaluating behavioral disorders and criminal propensities, showed the causes and types of behavioral disorders and criminal propensities in the Holy Qur’an, and focused on the Holy Qur’an’s properties in evaluating behavioral disorders and criminal propensities and the evaluation tools and standards of the Holy Qur’an. In addition, this study presented glimpses from the life of Allah’s Messenger (May Allah grant him blessings and peace) in dealing with behavioral disorders to demonstrate the prophetic methods and styles in treating behavioral disorders and criminal propensities. The study depended on a number of methodologies appropriate to the study’s subject and objectives, namely: the descriptive, analytical, inductive, and deductive methodologies, and the applied descriptive methodology for this study is applied on the Repentant Rehabilitation Center in Kuwait. The researcher prepared questionnaires and then distributed them on the center’s dwellers, then interviewed a group of the teachers, and finally attempted the statistical analysis of the applied study. The study aimed to clarify the means and methods that can be used in evaluating the behavioral disorders and criminal propensities, documenting the applications of the Qur’anic approach in treating the behaviorally disordered people and those with criminal tendencies, and highlighting the effect of applying the means and methods of the Holy Qur’an in evaluating behavioral disorders and criminal propensities among those enrolled in the Repentant Rehabilitation Center in the State of Kuwait, in order to circulate them to centers similar to the center in this study in order to lessen the crime rates. The study found the following results. the Holy Qur’an used many tools in evaluating the behavioral disorders and criminal propensities. There are standards that must be adhered to while using the Qur’anic approach in the evaluation process, so that the process proceeds in a correct manner and become fruitful. The Sunnah of Allah’s Messenger (May Allah grant him blessings and peace) represents the practical application of the Holy Qur’an in correcting behavioral disorders and criminal propensities. The researcher recommended the need to carry out encyclopedic studies that include the Qur’anic and Prophetic approaches in dealing with behaviorally disturbed people and those with criminal propensities. This encyclopedia includes the Qur’anic approach and its practical applications (the Prophet’s Sunnah), in order to reach a useful educational approach for this group.